Adaptive Autophagy Offers Cardiorenal Protection in Rats with Acute Myocardial Infarction - Zhendong Feng; Han Xue Jiang; Huiyang Chen; Yu Ning Liu; Yahui Wang; Rui Bing Yang; Xueting Han; Chen Hui Xia; Ze Bing Zhu; Hongcai Shang; Aiming Wu; Wei Jing Liu (Cardiology Research and Practice)
Objective. Understanding the multifactorial changes involved in the kidney and heart after acute myocardial infarction (AMI) is prerequisite for further mechanisms and early intervention, especially autophagy changes. Here, we discussed the role of adaptive autophagy in the heart and kidney of rats with AMI. Methods. A rat model of AMI was established by ligating the left anterior descending branch of the coronary artery. Animals were sacrificed at 2 and 4 weeks after the operation to assess the morphological and functional changes of the heart and kidney, as well as the autophagy pathway. In vitro, HK-2 and AC16 cell injuries and the autophagy pathway were assayed after autophagy was inhibited by 3-methyladenine (3-MA) in a hypoxia incubator. Results. We found that the left ventricular systolic pressure (LVSP) significantly decreased in the model group at weeks 2 and 4. At weeks 2 and 4, the level of urinary kidney injury molecule 1 (uKIM1) of the model group was significantly higher than the sham group. At week 4, urinary neutrophil gelatinase-associated lipocalcin (uNGAL) and urinary albumin also significantly increased. At week 2, microtubule-associated protein 1 light chain 3-II (LC3-II), ATG5, and Beclin1 were significantly elevated in the heart and kidney compared with the sham-operated rats, but there was no change in p62 levels. At week 4, LC3-II did not significantly increase and p62 levels significantly increased. In addition, 3-MA markedly increased KIM1, NGAL, and the activity of caspase-3 in the hypoxic HK-2 and AC16 cell. Conclusion. Autophagy will undergo adaptive changes and play a protective role in the heart and kidney of rats after AMI.